Interpersonal processes in paranoia: a systematic review. Issue 14 (20th March 2018) - Meisel, Susanne F.; Garety, Philippa A.; Stahl, Daniel; Valmaggia, Lucia R.
Abstract: Paranoid ideation is a core feature of psychosis, and models of paranoia have long proposed that it arises in the context of disturbances in the perception of the self. However, to develop targeted interventions, there is a benefit in clarifying further, which aspects of self-perception are implicated. Interpersonal sensitivity is a personality trait which has been associated with the risk of paranoid thinking in the general population. However, not all studies have found this link. We aimed to review the empirical literature assessing the association between interpersonal sensitivity and paranoia in both general population and clinical samples; and to explore if associations found differed depending on whether state or trait paranoia was assessed. The review followed PRISMA guidelines. Articles were identified through a literature search in OVID (PsychINFO, MEDLINE) and Web of Science up to December 2016. Fourteen studies with a total of 12 138 participants were included. All studies were of 'fair' or 'good' quality. A robust association was found between interpersonal sensitivity and paranoia in clinical and general population samples alike, regardless of the method of assessment of both paranoia and interpersonal sensitivity. Although this finding was more pronounced in studies of trait paranoia, it is likely that differences in study purpose, measurement, and power explain these differences. Findings from this review support the hypothesis that feelings of personal vulnerability and exaggerated socially evaluative concerns are central for both onset and maintenance of paranoid symptoms, suggesting avenues for future research in targeted interventions.